Quetiapine Inhibits Microglial Activation by Neutralizing Abnormal STIM1-Mediated Intercellular Calcium Homeostasis and Promotes Myelin Repair in a Cuprizone-Induced Mouse Model of Demyelination - Wang, Hanzhi; Liu, Shubao; Tian, Yanping; Wu, Xiyan; He, Yangtao; Li, Chengren; Namaka, Michael; Kong, Jiming; Li, Hongli; Xiao, Lan (Frontiers in Cellular Neuroscience, 2015)
Microglial activation has been considered as a crucial process in the pathogenesis of neuroinflammation and psychiatric disorders. Several antipsychotic drugs (APDs) have been shown to display inhibitory effects on microglial activation in vitro, possibly through the suppression of elevated intracellular calcium (Ca2+) concentration. However, the exact underlying mechanisms still remain elusive. In this study, we aimed to investigate the inhibitory effects of quetiapine (Que), an atypical APD, on microglial activation. We utilized a chronic cuprizone (CPZ)-induced demyelination mouse model to determine the direct effect of Que on microglial activation. Our results showed that treatment with Que significantly reduced recruitment and activation of microglia/macrophage in the lesion of corpus callosum and promoted remyelination after CPZ withdrawal. Our in vitro studies also confirmed the direct effect of Que on lipopolysaccharide (LPS)-induced activation of microglial N9 cells, whereby Que significantly inhibited the release of nitric oxide (NO) and tumor necrosis factor α (TNF-α). Moreover, we demonstrated that pretreatment with Que, neutralized the up-regulation of STIM1 induced by LPS and declined both LPS and thapsigargin (Tg)-induced store-operated Ca2+ entry (SOCE). Finally, we found that pretreatment with Que significantly reduced the translocation of nuclear factor kappa B (NF-κB) p65 subunit from cytoplasm to nuclei in LPS-activated primary microglial cells. Overall, our data suggested that Que may inhibit microglial activation by neutralization of the LPS-induced abnormal STIM1-mediated intercellular calcium homeostasis.